INCREASING CHILDREN'S INTEREST IN LEARNING THROUGH LEARNING METHODS WHILE SINGING IN ARISAN DERAS VILLAGE - Wike Wike; Wa Ode Riniati; Muwahidah Nurahasanah; Eka Adnan Agung; Afif Alfiyanto (Universitas Pahlawan Tuanku Tambusai, 2023)
Education is an obligation for every human being, and one way is by learning and considering that during the current pandemic, every school can only enter once a week. Therefore, one of the collaborative service programs between the research team and the people of Arisan Deras Village. The service activities provide learning related to increasing children's interest in learning in arisan deras village by using the learning method while singing. Through this method of learning while singing, the research team hopes to improve the quality and memory of children in Arisan Deras Village by studying religious science, Arabic, English, and technology so that they can easily remember and understand and memorize what they learn. At the time of its initial implementation, in the learning and teaching process, it was still seen that there were children who were not interested in participating in learning. But, after applying the learning method of singing, it turned out that children's interest in learning looked more enthusiastic. The results showed that children were more active and quick in understanding the material taught.